Quenching from the mushy state - a new technique for the production of metastable phases - Ramachandrarao P.; Lal K.; Singhdeo A.; Chattopadhyay K. (My University, 2025)
Liquids entrapped in solids are known to undercool drastically. This principle has been utilized in producing metastable phases in an Al-6.8 at.% Ge alloy. By holding the specimens at temperatures at which solid and liquid coexist and quenching them into water baths, undercooling is induced and two metastable phases with rhombohedral (a = 0.7672 nm and α = 96.55°) and monoclinic (a = 0.6734 nm, b = 0.5818 nm, c = 0.4282 nm and β = 88.96°) unit cells are produced. The metastable phases are identical to those obtained by splat quenching. © 1979.